Implementasi Restorative Justice Dalam Penyelesaian Tindak Pidana Ringan Berdasarkan Peraturan Kejaksaan Nomor 15 Tahun 2020 - Situmorang, Lasyohana; Aulia, Mega; Octavia, Dina; Audi, Ghita (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
The Republic of Indonesia Prosecutor's Office Regulation No. 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice is a significant milestone in the reform of the criminal justice system in Indonesia. This study aims to examine the implementation of the restorative justice concept in resolving minor crimes and to assess the effectiveness and challenges faced by law enforcement officials, particularly the prosecutor's office, in implementing this policy. The research method used is a normative juridical approach, using regulatory analysis, case studies, and interviews with legal practitioners. The results indicate that the application of restorative justice provides a more humane and efficient alternative for case resolution, oriented toward restoring relationships between perpetrators, victims, and the community. However, implementation in the field still faces obstacles such as a lack of understanding among officials, resistance to a retributive legal culture, and limited supporting facilities. Prosecutor's Office Regulation No. 15 of 2020 provides a clear legal framework, but synergy between institutions and public education are needed for the optimal implementation of restorative justice principles.